A Review of Markets for Clean Air: The U.S. Acid Rain Program by A. Denny Ellerman, Paul L. Joskow, Richard Schmalensee, Juan-Pablo Montero, and Elizabeth M. Bailey - Cramton, Peter (Journal of Economic Literature, 2000)
Markets for Clean Air is the definitive text on the U.S. acid rain program. This innovative program uses a cap-and-trade approach, rather than the traditional command-and-control approach, to reduce sulfur dioxide emissions. The authors conclude that the program was successful in cutting the costs of SO2 emission reductions by about half, saving tens of billions of dollars. Both scholars and policy makers will have a better sense of the virtues and pitfalls of market-based regulation after reading this.